Flexible product development : - Smith, Preston G. (Jossey-Bass, 2007)
This one, "Flexible Product Development: Building Agility for Changing Markets" is a book that describes a successful future of product development and project management. The flexibility concept Preston describes is essential to managing products and projects in the future. The speed of business continues to require teams to get projects done faster with less resources and information.